Effect of Frusemide on Pulmonary Blood Volume. Issue 5656 (31st May 1969) - Bhatia, M. L.; Singh, Inder; Manchanda, S. C.; Khanna, P. K.; Roy, Sujoy B.
Abstract : Intracardiac frusemide given to seven patients recovering from high-altitude pulmonary oedema caused a significant reduction in the pulmonary blood volume before the onset of diuresis. This supports the suggestion that the mobilization of fluid from the pulmonary circuit is responsible for the relief of symptoms in some patients with pulmonary oedema even when a diuresis does not occur.